Neck Swelling: Risk Factors and The Presence of The Thyroid Cancer - Nagah Bobtina; Ashraf M. Elmansori; Mohamed Bubteina (Journal of Libyan Academy Bani Walid, 2025)
Swellings in the neck are frequently encountered by surgeons in outpatient clinics in the hospitals. Given their visibility and potential cosmetic implications, these could be malignant tumors, often leading to prompt medical consultation. Aims This observational research aimed to analyze the clinical characteristics and underlying causes of neck masses in patients from Benghazi city. The age distribution and etiological factors of neck swelling across various age groups and genders were assessed as risk factors impacting patients. The study sought to explore the correlation between age, gender, and medical conditions contributing to neck swelling, such as thyroid cancer. The total number of patients who had neck swelling was 250. Approximately 103 had lymph node inflammation, and 127 cases had enlarged thyroid glands. While 5 cases were suffering from respiratory infections, 9 pertained to neck cancer, and 8 were linked with hematomas, accounting for around 40.2%, 50.8%, and 3.2% of cases, respectively. Most patients are female in the whole category, with critical ages in thyroid diseases from 31-39 years and in lymph nodes from ages 34-44 years. Bronchial infection from 33-44 years and cancer diseases from age 25-35 years, as well as hematomas between 29-39 years. The biopsies were taken from the patients who had thyroid cancer, and paraffin sections were prepared and examined under a microscope to identify the type of tumor. Data were analyzed using Excel, and the p-value was p < 0.05. As a result, most of the patients had thyroid disease. Additional research on this topic is essential to mitigate its adverse effects on public health in the future